Communication Using the Storytelling Method Improves Knowledge in Implementing Health Protocols for School-Age Children - Kili Astarani; Srinalesti Mahanani; Maria Anita Yusiana (Journal of Ners and Midwifery, 2023)
The continuous increase in confirmed cases of COVID-19, especially in children aged 6–18, has prompted the government to provide advice to the public on how to implement health protocols and have clean and healthy living habits, especially in terms of implementing health protocols. One of the approaches that can be taken to provide knowledge to children is by communicating using storytelling. By storytelling or telling stories about implementing health protocols, children can better accept and digest what is given. The purpose of this study was to analyze the effect of communication using the storytelling method on knowledge of implementing school-aged children's health protocols at SD Kalipang 4 Grogol, Kediri district. The research design used was the pre-experiment using the one-group pretest-post-test design method. The population of this study was school-age children at SD Kalipang 4 Grogol, Kediri Regency, with a total of 26 students. The independent variable used is storytelling on the application of the health protocol, and the dependent variable is knowledge of the implementation of the health protocol. The sampling technique used is total sampling. By using a knowledge questionnaire about implementing health protocols. Data analysis used the Wilcoxon statistical test to analyze the effect of communication using the storytelling method on knowledge of implementing health protocols. Conclusion Communication using the storytelling method affects school-age children's knowledge about implementing health protocols at SD Kalipang 4 Grogol, Kediri, with a significance value of 0.000 (p=0.05)